1994
DOI: 10.1159/000246790
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Malignant Melanoma Appearing during Photochemotherapy of Mycosis fungoides

Abstract: We report a case of malignant melanoma that appeared in a 56-year-old man with mycosis fungoides (stage la) during treatment with PUVA. The cumulative UVA dose was 1 177 J/cm2. The pigmented lesion was removed and PUVA therapy discontinued. Histological examination revealed a superficial spreading malignant melanoma (1.77 mm thick, Clark level IV). The delayed-type cutaneous hypersensitivity was studied. The presence of a second malignancy after mycosis fungoides and PUVA therapy may have been coincidental. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Of the 6 patients with melanoma, 3 had also been treated with PUVA and 2 with topical mechlorethamine. Other authors have also reported melanoma and MF in association, 5,6 and this has also been ascribed to the use of skin-directed treatments with carcinogenic potential. In addition to cutaneous malignancies there are reports of an increased incidence of internal malignancies for patients with CTCL.…”
Section: Discussionmentioning
confidence: 92%
“…Of the 6 patients with melanoma, 3 had also been treated with PUVA and 2 with topical mechlorethamine. Other authors have also reported melanoma and MF in association, 5,6 and this has also been ascribed to the use of skin-directed treatments with carcinogenic potential. In addition to cutaneous malignancies there are reports of an increased incidence of internal malignancies for patients with CTCL.…”
Section: Discussionmentioning
confidence: 92%
“…In these cases, some of the same pathologic links as those put forward to explain the increased incidence of nonmelanoma skin cancers in MF have been postulated, including effects of therapies for MF. Melanoma has been reported in several MF patients treated with PUVA therapy 2,4,6 . While PUVA increases the risk of nonmelanoma skin cancers, its association with malignant melanoma has not been definitively demonstrated 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This form of cancer is often fast‐growing and fatal. The literature contains a number of case reports on invasive cutaneous malignant melanomas 20 –28 but it has been difficult to determine whether these melanomas were induced by PUVA or were coincidental. Only one population‐based study has been published, 29 and for the first time it has shown an increased risk for malignant melanoma in patients treated with high cumulative doses of PUVA and, most important, after a latency period of at least 15 years.…”
Section: Discussionmentioning
confidence: 99%